The ethical community consultation model as preparation for nursing research: A case study - Freysteinson, Wyona M (Nursing ethics, 2010)
This article describes a case study in which community consultation was used to assist in the preparation of a research project on viewing self in the mirror after mastectomy. Breast cancer survivors, nurses, and other health care professionals were consulted using a variety of interactive modalities. Over a period of three months, pre-research planning information was obtained from participants. A descriptive qualitative design was used to analyze the data. The ethical goals of community consultation provided the framework for dialogue and the synthesis of information. During this project, the potential benefits of the proposed research study were explored. Possible risks to future participants were discussed, and recommendations for participant protection suggested. Community members provided insight into the legitimacy of the study. Community consultation is a tool that researchers may consider when designing studies.